PENGARUH MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Zuhrina Aidha (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2016)
ABSTRACT Entrepreneurship in Indonesia is still in below 2%. For comparison, entrepreneurship in the United States reached 11 percent of the total population, as much as 7 percent of Singapore, and Malaysia as much as 5 percent. The development of human resources with this kind of competition from the younger generation appropriate and relevant for the students to become entrepreneurs and create jobs. The purpose of this study to determine how the student interest in entrepreneurship UIN FKM-SU based on motivations. Indicator of entrepreneur motivation are Ambition for freedom, Self Realisation, and Pushing factors. This research is quantitative. Sample collection by distributing questionnaires, using a sampling method to 64 respondents totally student. The analysis technique used is a multivariate analysis with SPSS version 20 with an alpha of 5%. The results of this study indicate that entrepreneurship motivation of indicator Ambition for freedom that most influence on student interest in entrepreneurship UIN FKM-SU. Keyword : Motivation, interest, Entrepreneur, Entrepreneurship, Entrepreneurship Motivation